SELF-MEDICATION FOR PREVENTION AND TREATMENT OF DISEASES DURING COVID-19 PANDEMIC-A CROSS SECTIONAL SURVEY IN GENERAL POPULATION - PANIGRAHY, SARITA; DASS, DEEPANJANA; PANDEY, SUNIL KUMAR; SHEENA, DAMERA MEHER (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: The goal of this study was to assess the pattern and reasons for self-medication during the COVID-19 pandemic. Methods: The present study was an exploratory cross-sectional survey. The questionnaire was meant to be filled up by those who were older than 18 y and could read and write English. The questionnaire (related to socio-demographic status, pattern, and reasons for self-medication) was designed and validated by a committee of faculties in the department of pharmacology through a peer review process and sent through mail, WhatsApp, and other means of social media. A non-parametric Chi-square test was used to test relationships between categorical variables. Results: The responses of 557 participants were analyzed; among them, the majority were females as compared to males. There was a significant difference (*p = 0.02) in the pattern of self-medication between the males (38%) and females (62%), and most of the participants used self-medication as a preventive measure for COVID-19 (39%). Fear of going out (13%) during COVID-19 was the main single reason for self-medication. Arsenic Album 30 was the most frequently used homeopathic formulation (26%). Conclusion: This study showed that apprehension, coupled with the COVID-19 pandemic, was the main impulse for self-medication.